Estudio de productividad y rendimientos en procesos constructivos, mediante el uso de Grúa Torre - Mena-Cubero, Johan (Instituto Tecnológico de Costa Rica, 2007)
This project consisted of developing an analysis of the productivity and yields related to the operation of the tower crane. This included a breakdown of the principal activities that realizes its time designation during the day of work, its respective yield and productivity. The present study offers a general idea on the efficiency of this equipment, in the development of activities as the montage of prefabricated beams, montage of slabs, and others. Besides a realization of an analysis to determine the influence the aspects such as productivity and yields on the cost of operation for the tower crane, with base in the amount budget for this activity in the development of the Project EuroCenter, which constructs the company EDICA Ltda. By means of the elaboration of this project it determines that the tower crane operates on to 83.87 % and that the percentage of unproductive time is 16.13 %. Also one concluded that the cost of operation for the tower crane is of ¢ 95.777.000 in 10 months that it works during the development of the project, this transfers to an hourly cost of ¢ 36.279. In conclusion, It estimate that the cost which one incurs for concept of dead time is of ¢ 1.099.517 monthly, fact that affirms that it is indispensable to give it an ideal utilization to the tower crane.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2007.
Keywords: Costos; Desempeño; Tiempo; Procesos; Vigas